1" alt="\log_{3}(x+1) + \log_{3}(x+3) > 1" align="absmiddle" class="latex-formula">
Запишем ОДЗ: 0} \atop \bigg{x+3 > 0}} \right. \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x > -1} \atop \bigg{x > -3}} \right. \ \ \ \Rightarrow x > -1" alt="\left \{ {\bigg{x+1 > 0} \atop \bigg{x+3 > 0}} \right. \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x > -1} \atop \bigg{x > -3}} \right. \ \ \ \Rightarrow x > -1" align="absmiddle" class="latex-formula">
Упростим неравенство:
1\\\log_{3}(x+1)(x+3) > \log_{3}3\\(x+1)(x+3) > 3" alt="\log_{3}(x+1)(x+3) > 1\\\log_{3}(x+1)(x+3) > \log_{3}3\\(x+1)(x+3) > 3" align="absmiddle" class="latex-formula">
Объединим неравенство с ОДЗ:
-1 \ \ \ \ \ \ \ \ \ \ \ \ \ } \atop \bigg{\ (x+1)(x+3) > 3^{*}}} \right. \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x \in (-1; \ +\infty) \ \ \ \ \ \ \ \ \ \ \ \ \ \ } \atop \bigg{x \in (-\infty; \ -4) \cup (0; \ +\infty)}} \right.\\\\\Rightarrow x \in (0; \ +\infty)" alt="\left \{ {\bigg{x > -1 \ \ \ \ \ \ \ \ \ \ \ \ \ } \atop \bigg{\ (x+1)(x+3) > 3^{*}}} \right. \ \ \ \ \ \ \ \ \ \left \{ {\bigg{x \in (-1; \ +\infty) \ \ \ \ \ \ \ \ \ \ \ \ \ \ } \atop \bigg{x \in (-\infty; \ -4) \cup (0; \ +\infty)}} \right.\\\\\Rightarrow x \in (0; \ +\infty)" align="absmiddle" class="latex-formula">
Ответ:
* Решение данного неравенства упущено (оно решается методом интервалов или парабол).